The lexical representation of the concept "anguish" over the signs of bird. (Eurasian Journal of Philology Science and Education, 2015)
The scientific study investigates the problem of lexical representations of the concept "anguish" from the perspective of semantic-cognitive approach. The novelty of the research is to describe the cognitive model of lexicalsemantic field of the concept of "anguish" after signs of bird, which reflects the concept of the study in the linguistic consciousness of native speakers. In order to gain access to the content of the concept as thought units installed semantic scope of the concept as follows: direct nomination of the concept (keyword – represent of the concept,which is elected by the researcher as the name of the concept and the name of the nominative of the field, and its system synonyms); derivatives nomination concept (portable, derivatives); contextual synonyms; occasional individual authors nomination; metaphorical nomination; stable comparing with the keyword; figurative conceptualfeatures that characterize the concept, literary texts that reveal the content of the concept which suggests that the signs of the bird represented by the lexical synonyms, most accurately reflect the emotions and structured linguisticconsciousness.
Keywords: concept; semantic-cognitive approach; language awareness; lexical synonymy; the signs of the bird